(untitled) (World Science, 2022)
Relevance. The prevalence of posture defects, according to various researchers, is from 0.6% to 78%. The disruptions in the posture biomechanics leads to excessive stress on the main joints of the human body including temporomandibular joint. Objective. The research aimed to study the prevalence of violations of the anatomical and functional system "posture-occlusion" and the structure of early signs of degenerative-dystrophic changes in the spine in medical students. Materials and methods. 130 students of medicals and dental faculties (including 42 men and 88 women) with posture disorders were examined in accordance with special questionnaires developed at the department. The assessment of the functional state of the spinal was carried out using motor tests by the method of Goryana G.A. and complaints of pain according to the 10-point numerical scale of pain "NSP". The malocclusion was assessed according to the method of Khvatov depending on the type of mandibular displacement. Statistical analyses with program IBM SPSS Statistic Base v.22. Results. It has been found that 78 students or 60% did not have restricted and widespread osteochondrosis and pain degree was lower than 5 points. A high prevalence (40%) of combined deformity of posture and displacement of the lower jaw in combination with pain syndrome was established. Along with restricted osteochondrosis 38 (73,08%), distal type of lower jaw displacement was more commonly seen amongst students with postural defects 35 (67,31%). These clinically manifested a pain level of more than 5 points. Signs and symptoms of a combined pathology posture-occlusion were more common among women (37 patients, or 71.15%) than men (15 patients, or 28.85%)